The Use and Abuse of Sacred Places in Late Medieval Towns - Smet, Marjan de; Trio, Paul (Book collections on Project MUSE., 2006)
Church buildings dominated the medieval towns. Higher and stronger than most buildings in town, they offered a venue for various kinds of activities. Primarily the faithful flocked towards the churches to attend masses. However, the use of sacred places was not restricted to religion. Secular authorities, the ruler, the town government, the trades or guilds also made use of these ecclesiastical buildings for practical or socio-political reasons. As such the sacred places were perceived to lend a kind of sacral aura to all proceedings taking place inside. Apart from a mere enumeration and descr.